2002
DOI: 10.1038/oby.2002.152
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Restraint and Stress‐Induced Snacking in Youth

Abstract: ROEMMICH, JAMES N., SUZANNE M. WRIGHT, AND LEONARD H. EPSTEIN. Dietary restraint and stressinduced snacking in youth. Obes Res. 2002;10:1120 -1126. Objective: To determine whether dietary restraint modifies stress-induced eating in youth. Research Methods and Procedures: Snacking was measured in boys (9.5 Ϯ 0.3 years) and girls (9.0 Ϯ 0.3 years), with and without dietary restraint, across a control day after reading children's magazines and/or coloring, and on a stress day after giving a videotaped speech, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 27 publications
5
64
1
1
Order By: Relevance
“…Nevertheless, this has seldom been studied in young children. To our knowledge, only one study in preadolescents demonstrated more snacking with more perceived stress (Jenkins et al, 2005) and one study showed more snacking in response to laboratory stressors (Roemmich, Wright, & Epstein, 2002). Our findings add to this knowledge on the relationship between stress and an unhealthier diet, thereby differentiating for more food indices and more stress variables.…”
Section: Stress and Dietary Patternsmentioning
confidence: 54%
“…Nevertheless, this has seldom been studied in young children. To our knowledge, only one study in preadolescents demonstrated more snacking with more perceived stress (Jenkins et al, 2005) and one study showed more snacking in response to laboratory stressors (Roemmich, Wright, & Epstein, 2002). Our findings add to this knowledge on the relationship between stress and an unhealthier diet, thereby differentiating for more food indices and more stress variables.…”
Section: Stress and Dietary Patternsmentioning
confidence: 54%
“…Another potential mechanism is via increased psychological stress associated with TV viewing (for example of violent programmes) among children. 30 Given that there are links between stress and unhealthy diets in children, 31 the stress associated with TV viewing 30 may potentially lead to weight gain and sympathetic nervous system activation, both of which could mediate the relationship between TV viewing and elevated BP in children. 18 However, we did not assess the influence of dietary intake or indicators of psychological stress, and thus, cannot confirm the above hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been associated with depressive moods (Lee, Kim, Beck, Lee, & Oh, 2005). Additional research is needed to test whether depressive mood influences a variety of foods, in addition to the reinforcing value of sweet foods and whether the reinforcing value of food is increased under other psychological states that increase food intake, such as stress (Greeno & Wing, 1994;Roemmich, Wright, & Epstein, 2002).…”
Section: Depression and The Reinforcing Value Of Foodmentioning
confidence: 99%